Introduction to the special issue: The invisibility of the Realm of New Zealand - Leenen-Young, Marcia (Waka Kuaka, 2025)
The invisibility of the Realm of New Zealand in the historical and contemporary discourses about New Zealand mean there is limited understanding about what the Realm is. This special issue is a timely interrogation of this invisibility and the impacts it has had on Pacific peoples in the Realm, written by Pacific scholars who have ancestral connections to New Zealand’s imperial past. It asks, How do we grapple with the Realm of New Zealand as an invisible part of New Zealand’s contemporary reality and historical past as a colonial empire? This introduction addresses the contemporary importance of understanding the Realm of New Zealand, in legal and actual terms, laying a foundation for the complex discussions in this special issue.